Biological Efficacy and Toxicological Evaluation of Ethanolic Extract of Cassia nodosa Buch.-Ham. (Leguminosae) - Gameli Afu; Michael Konney Laryea; Lawrence Sheringham Borquaye (Journal of Chemistry, 2020)
Medicinal plants are used worldwide to treat various diseases. However, scientific validation of the therapeutic potential of most medicinal plants is absent, and little to no information on their potential toxicity exists. It is therefore important to assess the efficacy and toxicity of various medicinal plants commonly used in traditional herbal medicine. The main goal of this study was to evaluate the efficacy and toxicity of the ethanolic extract of Cassia nodosa, a plant used in the treatment of fever, cold, gastric pain, diabetes mellitus, and malaria in Ghana. The stem bark extract of Cassia nodosa was obtained by cold maceration. Following phytochemical examination via standard procedures, the extract was screened for antiplasmodial, anti-inflammatory, and antioxidant activities. The extract was also evaluated for acute oral toxicity and its toxicity to the liver and kidney of rats. Phytochemicals present in the extract included sterols, alkaloids, tannins, glycosides, and coumarins. In the in vitro antiplasmodial activity test, the Cassia nodosa extract showed moderate antiplasmodial activity with an IC50 value of 23.98 ± 2.07 µg/ml. An ED50 value of 8.52 ± 2.83 mg/kg in the anti-inflammatory test indicated that the Cassia nodosa extract administered orally was very active in reducing inflammation. The total antioxidant capacity of the extract was determined to be 48.49 ± 5.24 gAAE/100 g with the total phenolic content being 28.48 ± 3.13 (gGAE/100 g) extract. In the DPPH radical scavenging assay, the concentration required for 50% inhibition of DPPH radical was found to be 78.71 ± 6.84 µg/mL. There was a gradual increase in the body weight of rats in both treated and control groups during the acute toxicity test. Clinical biochemical tests did not show any significant differences between control and treated groups of animals in terms of liver and renal functions, 14 days after administration of Cassia nodosa extracts. Taken together, these results provide scientific validation for the use of the plant in traditional medicine.